Body composition of chronic renal patients: anthropometry and bioimpedance vector analysis - Viviane Soares; Ivan Silveira de Avelar; Sara Rosa de Sousa Andrade; Marcus Fraga Vieira; Maria Sebastiana Silva (Universidade de São Paulo, 2013)
OBJECTIVE: to compare the body composition of patients undergoing hemodialysis with that of healthy individuals using different methods. METHOD: cross-sectional study assessing male individuals using anthropometric markers, electrical bioimpedance and vector analysis. RESULTS: the healthy individuals presented larger triceps skinfold and arm circumference (p<0.001). The bioimpedance variables also presented significant higher values in this group. Significant difference was found in the confidence interval of the vector analysis performed for both the patients and healthy individuals (p<0.0001). The tolerance intervals showed that 55.20% of the patients were dehydrated, 10.30% presented visible edema, and 34.50% were within normal levels of hydration. Bioimpedance and vector analysis revealed that 52% of the patients presented decreased cell mass while 14.00% presented increased cell mass. CONCLUSIONS: the differences in the body composition of patients and healthy individuals were revealed through bioimpedance and vector analysis but not through their measures of arm circumference and arm muscle area.